Malignant acanthosis nigricans with oral manifestations in a young female: a case report and literature review - Liu, Zijian; Cao, Wuling (Frontiers in Oncology, 2024)
IntroductionAlmost all cases of malignant acanthosis nigricans with oral manifestations occurred in older age groups. Here, we report a case of malignant acanthosis nigricans in a young female presented with chief complaints of oral mucosal hyperplasia, who had previously been diagnosed with allergies.Case presentationA 30-year-old female developed oral hyperplasia and rash following seafood consumption, with subsequent resolution of the rash but persistent oral lesions and the appearance of pigmentation on her hands, neck, and axillae. Clinical examination revealed papillomatosis, hyperemia, and velvety hyperplasia in the oral cavity. Biopsy results confirmed papillary hyperplasia. Despite the patient’s belief in good health, she was advised to undergo further systemic examinations. Elevated serum tumor markers and histologic analysis of an endoscopic biopsy confirmed gastric cancer with duodenal infiltration, leading to the diagnosis of malignant acanthosis nigricans. Unfortunately, the patient passed away due to heart failure during chemotherapy treatment.ConclusionsThe majority of patients with malignant acanthosis nigricans present with oral lesions before the underlying malignancy is detected, emphasizing the importance of timely comprehensive systemic examination. Furthermore, our case suggests that age may not be a restrictive factor for the development of malignant acanthosis nigricans, and the presence of a rash can potentially obscure the cutaneous manifestations associated with this condition.